Emotional Engineering, Vol. 6 Understanding Motivation (Springer International Publishing, 2018)
This book looks back at the starting point of engineering to show the importance of motivation in dealing with the passive-to-active consumer change, and explains how engineering can be holistic. It presents a variety of research on emotion, discussing topics such as neuroscience, philosophy and physiology. In addition to providing similar research being carried out from different perspectives in other fields, it demonstrates to readers how they can work with researchers in other fields to explore the new frontiers and their applications together. With engineering quickly moving from product development to experience development, and the role of emotion in engineering becoming increasingly important, Emotional Engineering, Vol. 6 is a valuable resource for engineers and researchers. .